Improved prediction model for ceiling maximum smoke temperature in the uphill tunnel fires using water spray system - Jie Wang; Dan Huang; Yanlong Song; Kaihua Lu (Case Studies in Thermal Engineering)
Stack effect of sloped tunnel and cooling effect and dragging force induced by water spray system change smoke temperature which is a serious threat to the stability and integrity of the tunnel structure. Smoke temperature profile is investigated under various heat release rates (10 MW, 15 MW, and 20 MW), water spray flow rates (0, 100, 200, 300, and 400 L/min), and atomizing angles (0°, 30°, 60°, 90°, 120°, and 150°) at a constant slope of 3 %. The results reveal that the water spray system significantly suppresses the maximum temperature rise, particularly in the downstream area adjacent to the fire source, where the aggregation of smoke and the induced stack effect intensify the impact. Several dimensionless maximum temperature rise models were developed, incorporating a Q∗, q, and θ. The dimensionless maximum temperature rise adheres to an exponential decay function relative to the distance from the fire source, the index is −0.37, indicating a direct proportionality. This relationship is influenced by the heat absorption capacity of water spray droplets, which is a function of both the flow rate and the atomizing angle. Although the atomization angle has a minimal effect on the total heat absorption, it changes the spatial distribution of heat absorption, thereby affecting the smoke temperature curve. The flow rate is more important than the atomization angle in controlling smoke temperature. This predictive model is a reliable tool for estimating the maximum temperature rise in the upstream and downstream areas of the fire source under various water spray conditions.